PENERAPAN MODEL PEMBELAJARAN INDUKTIF KATA BERGAMBAR UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN PADA SISWA SEKOLAH DASAR SDN 004 LANGGINI - Sepni Harnida; Putri Hana Pebriana; Iis Aprinawati; Muhammad Syahrul Rizal; Yenni Fitra Surya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve students' initial reading skills through the Inductive Model with picture word media in class I students of UPT SDN 004 Langini in the 2024/2025 Academic Year. The type of research used is Classroom Action Research. The subjects of this study were 20 students, while the objects in this study were the Inductive Model of picture words and for students' beginner reading skills. In this study, 2 cycles were carried out, each cycle was carried out 2 meetings. Data collection techniques used in this study were observation, tests and documentation. Based on the increase in the number of students who achieved the learning objective achievement criteria (KKTP) and the increase in the average class and classical scores. The presentation value of classical completeness in cycle I meeting I was 40%, in cycle I meeting II 55%, and cycle II meeting I.65%, then in cycle II meeting II 80%. Based on the results of the study, it can be concluded that through the Inductive Model with Picture Word media, it can improve students' beginner reading skills in class I UPT SDN 004 Langgini.